The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/aud.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of the Narrative Embodied in the Hearing Aid Fitting Process on Treatment Outcomes

Abstract: This study suggests that the narrative embodied in a given fitting process can have a substantial effect on the perceived benefit of the treatment, independent of any acoustical differences, at least for experienced users. For first-time users, acclimatization seems to overshadow the purely narrative effect of any fitting process. In the future, research study designs should include steps to avoid narrative effects when technical parameters of hearing aids are the intended object of study. In clinical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…In contrast, significantly more woman than men were fit with a CI. Kaplan-Neeman et al [12] had more male patients with hearing aids in their study, similar to Naylor et al [42]. A binaural fitting and a longer time per day of use was related to higher satisfaction with hearing aids in the Kaplan-Neeman study [12].…”
Section: Hearing Aids/cissupporting
confidence: 66%
“…In contrast, significantly more woman than men were fit with a CI. Kaplan-Neeman et al [12] had more male patients with hearing aids in their study, similar to Naylor et al [42]. A binaural fitting and a longer time per day of use was related to higher satisfaction with hearing aids in the Kaplan-Neeman study [12].…”
Section: Hearing Aids/cissupporting
confidence: 66%
“…In the fourth study, new hearing aid users were the population of interest (Ferguson et al 2016). In the remaining study, the effects of audiologist interactions were studied among both experienced and new hearing aid users (Naylor et al 2015).…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Five studies were identified that included interventions employing: motivational engagement (Ferguson et al 2016), motivational interviewing (Aazh 2016a;Solheim et al 2018), diagnostic and interactive narratives (Naylor et al 2015) and performance perceptual counselling (Saunders and Forsline 2012) in relation to hearing aid use and benefit outcomes.…”
Section: Behaviours Of Hearing Healthcare Professionals and Hearing Amentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of counseling has been reported to patients with a history of hearing aids [81]. Patients between the two hearing aids with similar acoustic features reported differences in the quality of the sound because they were told at a consultation that these hearing aids are different.…”
Section: The Role Of Counseling and Audiologistmentioning
confidence: 99%